Graphene‐Assisted Preparation of In Situ TiC–TiB2/Al Composite Inoculant for Al–Si Alloy. Issue 11 (27th August 2019) - Li, Chongchao; Cui, Chunxiang; Wang, Xin; Zhao, Lichen; Liu, Shuiqing; Cui, Sen; Han, Binghao; Xia, Yuhang
Abstract : An in situ TiC–TiB2 /Al composite inoculant is prepared by melt spinning the sintered mixture of Al powder, Ti powder, B4 C particles, and graphene nanoplates (GNPs). To increase the degree of dispersion of the particles, the GNPs are coated on the surface of the B4 C particles by high‐energy ball milling before sintering. The as‐spun inoculant ribbons are added to the melt of a typical Al–Si alloy to verify its effect of refining the grains on aluminum alloys. It is found that the columnar grains of the as‐cast Al–Si alloy sample are refined to finely approximate equiaxed grains, with an addition level of 0.6 wt% of the inoculant ribbons. The mechanical properties of the as‐inoculated Al–Si alloys also improve significantly, and show a remarkable strengthening and toughening effect. It can be attributed to the grain refinement and the dispersion strengthening by the introduction of TiC and TiB2 particles in the Al matrix. The results show that the newly developed composite inoculant ribbons using GNPs can significantly meliorate the overall mechanical performance of typical Al–Si alloys. Abstract : The in situ TiC–TiB2 /Al inoculant ribbon is prepared through ball milling, sintering, and melt spinning. Transmission electron microscopy (TEM) shows that the lattices of TiC and Al with an isomorphic feature are almost completely matched. The mechanical properties of Al–Si alloy can be improved by adding TiC–TiB2 /Al inoculant ribbon.